2021
DOI: 10.1186/s12909-021-02596-w
|View full text |Cite
|
Sign up to set email alerts
|

Perception of pharmacy students towards their community pharmacy training experience: a cross-sectional study from Jordan

Abstract: Background The fact that pharmacists are in the front line of patients’ care gives a great responsibility to focus on education and training of pharmacy students to build a ‘patient-centered’ clinicians. Unfortunately, pharmacy education in the developing countries, have been lagging behind actual practice delivered by pharmacists. This highlighted the need to evaluate the perceptions of undergraduate pharmacy students regarding their current pharmacy training practices and experiences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…To this end, the course must possess avenues where students can communicate freely about their learning styles. A survey among 202 Jordanian pharmacy students found that learning tools and adopting specific behaviours and study habits promoted by their institution's learning centers enhance student performance (Abu Farha et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, the course must possess avenues where students can communicate freely about their learning styles. A survey among 202 Jordanian pharmacy students found that learning tools and adopting specific behaviours and study habits promoted by their institution's learning centers enhance student performance (Abu Farha et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The literature was reviewed 2,11,17,18 and a published questionnaire by Abufarha et al 13 which evaluated the perceptions of undergraduate pharmacy students regarding their current conventional pharmacy training practices was adopted to develop the online survey that suits the aim of this study. The final version of the survey was designed using the general principles of good survey design.…”
Section: Survey Development Validation and Reliabilitymentioning
confidence: 99%
“…Similar to other academic courses, this field training was utterly switched to a virtual training modality in order to reduce the risk of infection. 13 Another measurement that can be taken into consideration as a result of the new pandemic is the mental health of the students, which has a high impact on their learning process. 14 A recent study evaluated the stress levels among Indian students, any psychological imbalances, and their major hurdles during the CoViD-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%